2004
DOI: 10.1104/pp.103.031948
|View full text |Cite
|
Sign up to set email alerts
|

Hyperaccumulation of Cadmium and Zinc in Thlaspi caerulescens and Arabidopsis halleri at the Leaf Cellular Level

Abstract: Vacuolar compartmentalization or cell wall binding in leaves could play a major role in hyperaccumulation of heavy metals. However, little is known about the physiology of intracellular cadmium (Cd) sequestration in plants. We investigated the role of the leaf cells in allocating metal in hyperaccumulating plants by measuring short-term 109 Cd and 65 Zn uptake in mesophyll protoplasts of Thlaspi caerulescens "Ganges" and Arabidopsis halleri, both hyperaccumulators of zinc (Zn) and Cd, and T. caerulescens "Pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
133
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(147 citation statements)
references
References 61 publications
12
133
0
Order By: Relevance
“…Further confirmation by measuring the content of amino acids concluded that only 2.13% of the amino acids present in the Cd treated leaf samples were thiol containing cysteic acid. Cosio et al (2004) found that Cd accumulation increases in T. caerulescens 'Ganges' and decreases in A. halleri protoplasts indicating that Cd-permeable transport proteins are differentially regulated. They also concluded that Cd could be transported by a Zn and Ca pathway in Thlaspi caerulescens 'Prayon', whereas in 'Ganges', Cd was transported by other pathways (Cosio et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Further confirmation by measuring the content of amino acids concluded that only 2.13% of the amino acids present in the Cd treated leaf samples were thiol containing cysteic acid. Cosio et al (2004) found that Cd accumulation increases in T. caerulescens 'Ganges' and decreases in A. halleri protoplasts indicating that Cd-permeable transport proteins are differentially regulated. They also concluded that Cd could be transported by a Zn and Ca pathway in Thlaspi caerulescens 'Prayon', whereas in 'Ganges', Cd was transported by other pathways (Cosio et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Cosio et al (2004) found that Cd accumulation increases in T. caerulescens 'Ganges' and decreases in A. halleri protoplasts indicating that Cd-permeable transport proteins are differentially regulated. They also concluded that Cd could be transported by a Zn and Ca pathway in Thlaspi caerulescens 'Prayon', whereas in 'Ganges', Cd was transported by other pathways (Cosio et al, 2004). Thus, Cd uptake mechanisms might vary from one species of plant to another.…”
Section: Discussionmentioning
confidence: 96%
“…First, the mesophyll protoplasts were prepared from leaves according to the protocol described in Cosio et al (2004) and subsequently, the intact chloroplasts were obtained according to the method of Fitzpatrick and Keegstra (2001). The collected protoplast pellet was resuspended briefly in 300 mM sorbitol, 20 mM Tricine-KOH, pH 8.4, 10 mM EDTA, 10 mM NaHCO 3 , 0.1% (w/v) bovine serum albumin, and forced twice through 20-and 11-mm nylon mesh.…”
Section: Chloroplast and Envelope Membrane Preparationmentioning
confidence: 99%
“…The formation of Fe plaques on aquatic plants roots has been also reported (Povidisa et al, 2009) and this probably difficult the exactitude in quantifying this metal. When another hyperaccumulator (Arabidopsis halleri) was submitted to growth in a hydroponic solution containing Cd and Zn, the cell walls of epidermal cells retained practically all these ions, suggesting that accumulation of these metals may be due to the precipitation of Cd and Zn phosphate in the cell wall of (Cosio et al, 2004). However, when metals enter in the cell, in general they are restrained in vacuole, in a process crucial of detoxification.…”
Section: Discussionmentioning
confidence: 99%